Эволюция и применение ASP.NET в современном веб-пространстве - Бабаев Али Рамизович (Foundations and Trends in Research, 2025)
The continuous evolution of web technologies has significantly influenced the way organizations develop and maintain online platforms. As a core part of the Microsoft .NET ecosystem, ASP.NET offers a robust framework for building scalable, secure, and high-performance web applications. Combining server-side rendering capabilities with a broad set of tools and libraries, ASP.NET remains a versatile solution for both small-scale projects and large enterprise systems. This summary explores the key structural elements of ASP.NET, its integration with the .NET platform, and the fundamental security mechanisms that help protect data and maintain reliability in modern web environments. The following questions are addressed: Why has ASP.NET become a cornerstone of contemporary web development? What challenges do developers encounter when implementing advanced .NET solutions? How does ASP.NET ensure scalability, performance, and security? What new directions are shaping the future of ASP.NET within the .NET ecosystem?